1989
DOI: 10.1128/iai.57.1.95-99.1989
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sodium dodecyl sulfate-stable Bacteroides gingivalis proteases by polyacrylamide gel electrophoresis

Abstract: Profiles of the proteolytic activities found in Bacteroides gingivalis culture supernatants, outer membranes, vesicles, and cell extracts were analyzed in sodium dodecyl sulfate-polyacrylamide gels containing covalently bound bovine serum albumin. A total of eight distinct bands of proteolytic activity could be detected. Four of these were found in the culture supernatant (P1, P2, P3, and P4). The outer membranes, vesicles, and the cell extract each contained seven major proteolytic bands (P1, P3, P4, P5, P6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
2

Year Published

1990
1990
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 21 publications
(27 reference statements)
3
69
2
Order By: Relevance
“…A large increase in the number of C3 molecules bound to W83 was, however, noted in assays carried out in the presence of the protease inhibitor TLCK (30). We found that the presence of this inhibitor, and other known inhibitors of the proteolytic activity oi P. gingivalis (13,19), during opsonization did not increase the phagocytosis of the strain W83. This suggests that opsonically active C3 was not attached to the true external surface of the bacterial cells as has been shown for encapsulated bacteria (31).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…A large increase in the number of C3 molecules bound to W83 was, however, noted in assays carried out in the presence of the protease inhibitor TLCK (30). We found that the presence of this inhibitor, and other known inhibitors of the proteolytic activity oi P. gingivalis (13,19), during opsonization did not increase the phagocytosis of the strain W83. This suggests that opsonically active C3 was not attached to the true external surface of the bacterial cells as has been shown for encapsulated bacteria (31).…”
Section: Discussionmentioning
confidence: 70%
“…A number of studies have shown that there is a considerable variation in virulence between strains within the species and it has been suggested that this may be due to differences in collagenolytic and proteolytic activities (16,17). However, recent results indicate that the protease and collagenolytic activities do not account for the diflferences between the invasive and non-invasive strains (18,19). It has also been suggested that differences in virulence might be due to the degree of encapsulation and resistance to phagocytosis (20)(21)(22).…”
mentioning
confidence: 99%
“…Enzyme activity was demonstrated by a modification of the method of Kelleher & Juliano [8] and Grenier et al [12].…”
Section: Demonstration Of Enzyme Activitymentioning
confidence: 99%
“…P. gingivalis synthesizes a number of different proteolytic enzymes. However, no major differences in the protease profile have so far been found which may differentiate between the virulent and avirulent strains within the species [72]. Proteinases from black-pigmented Gram-negative anaerobes can degrade human plasma proteins.…”
Section: Enzymatic Activitymentioning
confidence: 99%